2020
DOI: 10.1101/2020.11.09.374231
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel proteostasis reporter mouse reveals different effects of cytoplasmic and nuclear aggregates on protein quality control in neurons

Abstract: The cellular protein quality control machinery is important for preventing protein misfolding and aggregation, and decline in protein homeostasis (proteostasis) is believed to play a crucial role in age-related neurodegenerative disorders. However, how proteostasis capacity of neurons changes in different diseases is not yet sufficiently understood, and progress in this area has been hampered by the lack of tools to monitor proteostasis in mammalian models. Here, we have developed reporter mice for in vivo ana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…2 Although the PN robustly safeguards the proteome early in life, the capacity of the PN to maintain proteostasis declines abruptly during adulthood in worms, flies, and mice, leaving cells and tissues more vulnerable to the accumulation of toxic protein species with age. [4][5][6][7] Attempts to understand the basis of proteostasis collapse in the nematode worm Caenorhabditis elegans have revealed that proteostasis capacity declines as animals commit to reproductive maturity. 8,9 This is preceded by a rapid decline in the ability of the transcription factor HSF-1 to drive the expression of PN genes, most notably those encoding for small heat shock proteins (sHSPs) and HSP-70 family members.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although the PN robustly safeguards the proteome early in life, the capacity of the PN to maintain proteostasis declines abruptly during adulthood in worms, flies, and mice, leaving cells and tissues more vulnerable to the accumulation of toxic protein species with age. [4][5][6][7] Attempts to understand the basis of proteostasis collapse in the nematode worm Caenorhabditis elegans have revealed that proteostasis capacity declines as animals commit to reproductive maturity. 8,9 This is preceded by a rapid decline in the ability of the transcription factor HSF-1 to drive the expression of PN genes, most notably those encoding for small heat shock proteins (sHSPs) and HSP-70 family members.…”
Section: Introductionmentioning
confidence: 99%